MODERN POLITICAL CONCEPTS IN THE SOCIAL NETWORKS THEORY - Березовська-Чміль, О. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the essential characteristics of social networks and conceptual basis of their research. The main parameters and features network structures as factors of political influence, their advantages and disadvantages. The modern aspects of development of the social network theory are analyzed in this work.